2013
DOI: 10.1007/s11604-013-0245-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-occlusive mesenteric ischemia (NOMI): utility of measuring the diameters of the superior mesenteric artery and superior mesenteric vein at multidetector CT

Abstract: D and D were significantly smaller in NOMI patients than in the controls and D is a more significant parameter than D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 22 publications
0
26
1
2
Order By: Relevance
“…Denn die eingeschlossenen Patientenzahlen der o. g. Studien belaufen sich nur auf 11 -28 Patienten. So wurden in der Studie von Nakamura und Mitarbeitern 11 Patienten mit einer NOMI mit einer Vergleichsgruppe von 44 Patienten im CT verglichen [8]. Dabei wurden die Durchmesser der V. und der A. mesenterica superior im CT miteinander verglichen.…”
Section: Computertomografieunclassified
“…Denn die eingeschlossenen Patientenzahlen der o. g. Studien belaufen sich nur auf 11 -28 Patienten. So wurden in der Studie von Nakamura und Mitarbeitern 11 Patienten mit einer NOMI mit einer Vergleichsgruppe von 44 Patienten im CT verglichen [8]. Dabei wurden die Durchmesser der V. und der A. mesenterica superior im CT miteinander verglichen.…”
Section: Computertomografieunclassified
“…2 The findings of ischemic bowel disease such as asymmetric enhancement (decreased or increased) of segments of the bowel wall, localized mesenteric fluid or edema, pneumatosis intestinalis, portal venous gas, high attenuation of the bowel wall on unenhanced CT scans, bowel wall thickening (2 mm), or thinning (paper-thin wall) in the presence of patent mesenteric arteries and veins raise the suspicion of NOMI. 8 CT is highly sensitive and accurate in detecting central occlusions of the mesenteric arteries and veins. 2 CT is also helpful in differentiating high-grade stenosis from occlusion of the superior mesenteric artery (SMA), especially with the use of sub-volume multiplanar reconstructions.…”
Section: Computed Tomographymentioning
confidence: 99%
“…Multiple studies reported the utility of MDCT and threedimensional (3D) reconstructions in establishing the diagnosis of NOMI in clinically suspected patients. 5,[8][9][10] Multiplanar reconstructions and 3D volume rendered images allow detection of narrowing of the SMA, irregularities of branch vessels, spasm of the arcades of the SMA, and visibility of intramural vessels. 9,10 The mean diameter of SMA in NOMI patients was reported to be 3.4 AE 1.1 mm, compared with 6.0 AE 1.5 mm in normal patients.…”
Section: Computed Tomographymentioning
confidence: 99%
“…Y. Nakamura и соавт. [45] проанализировали диаметр ВБА и верхней брыжеечной вены у пациентов с неокклюзионной формой ОНМзК. Авторами был выявлен достоверно меньший диаметр указанных сосудов при этом заболевании по сравнению с нормальными значениями, а диаметр верхней брыжеечной вены был более прогностически значимым критерием, чем диаметр ВБА.…”
Section: хирургия 1 2017unclassified